2021
DOI: 10.1111/nuf.12678
|View full text |Cite
|
Sign up to set email alerts
|

Concept analysis of longitudinal assessment for professional continued certification

Abstract: Background: This concept analysis presents a scholarly epistemological approach to defining the attributes, empirical referents, antecedents, and consequences of a knowledge maintenance approach-known as longitudinal assessment-to professional certification.Aim: The analysis reports on the efforts of the National Board of Certification and Recertification for Nurse Anesthetists to explore this educational method as an approach to meet requirements for continued professional certification.Method: Using the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Studies have shown that spaced learning (exposure to materials interspersed with other activities), repeated testing, and interleaving of content (simultaneously presenting several different learning topics) improves knowledge retention by improving the brain's ability to differentiate between concepts, thereby strengthening memory associations 1 (Anzia, 2021;Brennan et al, 2004;Brown et al, 2014;Griffis et al, 2022;Price et al, 2018;Reid et al, 2018). Compared to studying content in blocks of time, interleaving allows for better knowledge retention due to studying related but distinct content over time, a concept that is similar to LA in that learning and testing occur in spaced increments (Price et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that spaced learning (exposure to materials interspersed with other activities), repeated testing, and interleaving of content (simultaneously presenting several different learning topics) improves knowledge retention by improving the brain's ability to differentiate between concepts, thereby strengthening memory associations 1 (Anzia, 2021;Brennan et al, 2004;Brown et al, 2014;Griffis et al, 2022;Price et al, 2018;Reid et al, 2018). Compared to studying content in blocks of time, interleaving allows for better knowledge retention due to studying related but distinct content over time, a concept that is similar to LA in that learning and testing occur in spaced increments (Price et al, 2018).…”
mentioning
confidence: 99%
“…In 2018, the Rand Corporation reported on the use of longitudinal assessment (LA) amongst healthcare professions, and the emergence of LA as pilot studies within the ABMS member boards and the National Commission on Certification of Physician Assistants (NCCPA) (Reid et al, 2018). Longitudinal assessment is an evaluation method that assesses learning acquired over-time, is more formative in nature, and has an intent of identifying knowledge gaps and opportunities for continuing education (ACICBL, 2011;Griffis et al, 2022;Price et al, 2018). Longitudinal assessments are shorter assessments administered repeatedly over a defined period of time on a broad range of topics determined by the needs of the profession, healthcare practitioners, or public (Giron et al, 2021).…”
mentioning
confidence: 99%